Directive Speech Act as Found in the Message Film by Moustopha Akkad - Laelam Musfiroh; Sufiyandi Sufiyandi; Rini Afrilesa J (Krinok:Jurnal Linguistik Budaya, 2020)
This study focus on directive as Found in the Message Film. It tells about kind of directive in Message Film Moustopha Akkad. The aims of this research are: (1) to find illocutionary Directive speech act as found in the Message Film (2)to find types of directivespeech in the Message Film byMoustopha Akkad. The data of this research is dialogues of Message filmMoustopha Akkad.hutang budiThis research uses qualitative research as method and it has 3 procedures; they are collecting data, analyzing the data and data presentation. In collecting the data, it used observation method from Sudaryanto (1993) as main method where uses non-participant observational method. The technique of collecting the data, itused download , watchingand note taking technique method. In analyzing the data, the data the writer uses Sudaryanto‘s theory, it is referential. The last procedure is data presentation is presented by using informal as Sudaryanto’s method.As John Searle’s theory has been used, the writer gets the result of the analysis found 4 kinds of directive uttered in Message Film Moustopha Akkad.. There are 46 data involve command24 data (52,17%), 11 data (23,91%) belong to suggestion, 7 data (15,21%) belong to warning,and4 data (8,69%) belong to request.Key word:speech Act, context, illocutionary, directive